Wind Driven Doubly Fed Induction Generator Grid Synchronization and Control - Abdelbaset, Adel (Power Systems,, 2018)
This book presents a modified model reference adaptive system (MRAS) observer for sensorless vector control of a wind driven doubly fed induction generator (DFIG). A mathematical model of the DFIG as influenced by core loss and main flux saturation is developed. The authors describe and evaluate grid synchronization enhancement of a wind driven DFIG using adaptive sliding mode control (SMC). Besides, grid synchronization of a wind driven DFIG under unbalanced grid voltage is also fully covered in this book.